2021
DOI: 10.3389/fped.2020.609279
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin in Combination With Standard Blood Tests in the Diagnosis of Inflammatory Bowel Disease in Children

Abstract: Introduction: Fecal calprotectin (FC) is a useful non-invasive screening test but elevated levels are not specific to inflammatory bowel disease (IBD). The study aimed to evaluate the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of FC alone or FC in combination with other standard blood tests in the diagnosis of IBD.Methods: Children aged <17 years who had FC (normal range <50 μg/g) measured and underwent endoscopy over 33 months in Christchurch, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…While a low calprotectin decreases the chances of IBD (particularly in combination with a low CRP), it does not eliminate IBD from the diagnosis; similarly an elevated calprotectin does not necessarily indicate IBD, particularly in patients with diarrhea-predominant IBS. 55 , 58 , 61 While most studies do not support a relationship between celiac disease and pediatric FAPDs, one Italian study found a 4-fold increase in celiac (4.4% vs 1%) in youth with IBS and another study found a borderline increase. 62 , 63 Both the American Gastroenterological Association (AGA) and the pediatric Rome committee have recommended celiac screening in IBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a low calprotectin decreases the chances of IBD (particularly in combination with a low CRP), it does not eliminate IBD from the diagnosis; similarly an elevated calprotectin does not necessarily indicate IBD, particularly in patients with diarrhea-predominant IBS. 55 , 58 , 61 While most studies do not support a relationship between celiac disease and pediatric FAPDs, one Italian study found a 4-fold increase in celiac (4.4% vs 1%) in youth with IBS and another study found a borderline increase. 62 , 63 Both the American Gastroenterological Association (AGA) and the pediatric Rome committee have recommended celiac screening in IBS.…”
Section: Discussionmentioning
confidence: 99%
“…While a low calprotectin decreases the chances of IBD (particularly in combination with a low CRP), it does not eliminate IBD from the diagnosis; similarly an elevated calprotectin does not necessarily indicate IBD, particularly in patients with diarrhea-predominant IBS. 55,58,61 While most studies do not support a relationship between celiac disease and pediatric…”
Section: Discussionmentioning
confidence: 99%
“…2G). Since fecal calprotectin (S100A8/ S100A9) is a useful screening biomarker for PIBD diagnosis in clinical practice [12,13,16], we compared the diagnostic efficacy of FCN1 with that of S100A8 and S100A9 to determine the potential clinical value of FCN1. In the colon validation set, S100A8 and S100A9 showed efficient diagnostic performance in PIBD, yielding AUCs of 0.920 and 0.877 respectively.…”
Section: The Mucosal-based Diagnostic Performance Of Fcn1 For Pibd Is...mentioning
confidence: 99%
“…Fecal calprotectin is the most documented non-invasive marker for IBD [12,13]. The use of fecal calprotectin in addition to symptoms improves the diagnostic accuracy of PIBD [14], but some PIBD patients have normal fecal calprotectin levels [15,16]. Therefore, it is still necessary to identify novel useful markers for early diagnosis of PIBD.…”
Section: Introductionmentioning
confidence: 99%
“…In diagnostic practice, fecal calprotectin has shown utility as a marker of intestinal inflammation. Notably, fecal calprotectin distinguishes between IBD, which is marked by increased gut permeability, from functional gastrointestinal disorders (4547) . Together, fecal calprotectin’s abundance, stability, and specificity position it as a strong biomarker of intestinal permeability.…”
Section: Introductionmentioning
confidence: 99%